Mediating roles of willingness to communicate and motivation in L2 learners’ second language communication in online contexts - Balouchi, Shima (2022)
The ideas of second language acquisition (SLA) and language communication have become so inextricably intertwined that previous language education research revealed that the path to second language (L2) learning passes via L2 speech. To date, a significant number of studies have highlighted the importance of affective variables in predicting students’ L2 communication in different contexts and with different participants; however, the relationship between learners’ affective variables and their L2 frequency of communication (L2 FOC) in fully online contexts has not been adequately investigated. Therefore, the main objective of the present study was to investigate the relationships between the L2 learners’ affective factors and their L2 frequency of communication in online contexts. This study also examined the mediating roles of learners’ L2 Willingness to Communicate (WTC) and L2 motivation on the relationship between L2 Self-Perceived Communication Competence (SPCC), L2 anxiety, international posture, and the L2 frequency of communication. This study’s variables are derived from Gardner’s (1985) socio-educational model of L2 learning, MacIntyre and Charos’ (1996) WTC model, and the concept of international posture (Yashima, 2000; 2004) in the field of social psychology and communication. This study employed an online questionnaire to collect data from L2 undergraduates, and graduate students enrolled in four top research universities in Malaysia. The partial Least Squares Structural Equation Modelling (PLS-SEM) approach was used to analyse the final data, which were 564 questionnaires. The findings of this study provide strong support for the proposed model and the hypothesised relationships. Furthermore, all of the direct established path’s hypotheses were supported, with the exception of the path from anxiety to L2 communication frequency. Further investigation into the mediating effects of L2 motivation and L2 WTC revealed that all but one of the mediation effects among the constructs were significant. The indirect effect of international posture on L2 communication frequency via L2 WTC was not supported. Therefore, 15 out of 17 established paths hypotheses were supported. As a result, the proposed structural model of this study had a strong statistical ability in describing, explaining, and predicting L2 frequency of communication in online contexts among tertiary students in Malaysia. These findings hold important implications for both theory and practice. It extends the application of Gardner’s (1985) socio-educational model and MacIntyre and Charos’ (1996) WTC model beyond the classroom setting to online contexts. Given the importance of L2 SPCC, lack of L2 anxiety, international posture, motivation, and L2 WTC in students’ L2 frequency of communication, those involved should consider developing and implementing activities that promote L2 SPCC, international posture, motivation, and L2 WTC while reducing L2 anxiety.